PELAKSANAAN PEMANFAATAN BARANG MILIK NEGARA MELALUI SEWA PADA KANTOR PELAYANAN KEKAYAAN NEGARA LELANG SURAKARTA - FADELI, FERI (Dinamika Hukum, 2020)
This study aims to identify and analyze the implementingon utilization of state property through rent and identify obstacle the implementingon utilization of state property through rent, in addition, this study also aims to determine the form the implementation monitoring of the utilization of state property at KPKNL Surakarta. This research is a type of empirical / sociological legal research and when viewed from the nature of the study is descriptive research. Research location in Surakarta KPKNL. The type of data used includes primary data and secondary data. Data collection techniques used are observation, interview and group discussion forums (FGD), literature studies in the form of legislation, books, journals and other documents that are relevant and related to the writing of this law. Data analysis uses qualitative data analysis. The results of this study indicate that the Implementation of Utilization of State Property through leases at the KPKNL Surakarta is accordance with the applicable rules, but there are still obstacles to the implementation of Utilization of State Property through leases at the KPKNL Surakarta i.e. obstacles in the form of legal substance, obstacles in the form of legal structure and obstacles in the form of legal culture. Supervision of the utilization of the lease implementation is carried out with an internal supervision model, for external supervision it has not been implemented given the lack of regulations that govern it Keywords: KPKNL Surakarta, utilization of state property through rent, Obstacles